1,10-Phenanthroline-5,6-Dione–Based Compounds Are Effective in Disturbing Crucial Physiological Events of Phialophora verrucosa - Granato, Marcela Queiroz; Gonçalves, Diego de Souza; Seabra, Sergio Henrique; McCann, Malachy; Devereux, Michael; dos Santos, André Luis Souza; Kneipp, Lucimar Ferreira (Frontiers in Microbiology, 2017)
Phialophora verrucosa is a dematiaceous fungus able to cause chromoblastomycosis, phaeohyphomycosis and mycetoma. All these fungal diseases are extremely difficult to treat and often refractory to the current therapeutic approaches. Therefore, there is an urgent necessity to develop new antifungal agents to combat these mycoses. In this context, the aim of the present work was to investigate the effect of 1,10-phenanthroline-5,6-dione (phendione) and its metal-based derivatives [Ag(phendione)2]ClO4 = ([Ag(phendione)2]+) and [Cu(phendione)3](ClO4)2.4H2O = ([Cu(phendione)3]2+) on crucial physiological events of P. verrucosa conidial cells. Using the CLSI protocol, we have shown that phendione, [Ag(phendione)2]+ and [Cu(phendione)3]2+ were able to inhibit fungal proliferation, presenting MIC/IC50 values of 12.0/7.0 µM, 4.0/2.4 µM and 5.0/1.8 µM, respectively. [Cu(phendione)3]2+ had fungicidal action and when combined with amphotericin B, both at sub-MIC (½×MIC) concentrations, significantly reduced (∽40%) the fungal growth. Cell morphology changes inflicted by phendione and its metal-based derivatives was corroborated by scanning electron microscopy, which revealed irreversible ultrastructural changes like surface invaginations, cell disruption and shrinkages. Furthermore, [Cu(phendione)3]2+ and [Ag(phendione)2]+ were able to inhibit metallopeptidase activity secreted by P. verrucosa conidia by approximately 85% and 40%, respectively. Ergosterol content was reduced (∼50%) after the treatment of P. verrucosa conidial cells with both phendione and [Ag(phendione)2]+. To different degrees, all of the test compounds were able to disturb the P. verrucosa conidia-into-mycelia transformation. Phendione and its Ag+ and Cu2+ complexes may represent a promising new group of antimicrobial agents effective at inhibiting P. verrucosa growth and morphogenesis.